Tafsir Jalal al-Din al-Suyuti dan Ibn Jarir al-Tabari pada al-Maidah/ 5: 51: Studi Tafsir Muqaran - Komarudin, Komarudin (Al Ashriyyah, 2022)
This article aims to reveal the interpretation of Jalaladdîn al-Suyûtî and Ibn Jarîr al-Tabarî about making Jews and Christians as leaders through their interpretation of the Qur'an in Surah al-Mâidah verse 51 and introduce the interpretation of muqāran. In fact, much literacy regarding to interpretations of al-Maidah verse 51 have been found, but among these literacies do not show the main source so that it feels far from substance. Helmy Zakaria for example, he wrote “Variety of Netizen's Interpretations About Non-Muslim Leaders; Study on the Interpretation of Surah al-Maidah verse 51 " This article is packaged using a qualitative method which is began by dissecting the works of al-Suyûtî and al-Tabarî; al-Dârr al-Mantsûr fî Tafsr al-Mantsûr and Jâmi' al-bayân fî Tawîl al-Qurân. Then it is compared, analyzed, and conluded. This article concludes that Ibn Jarîr al-Tabarî and Jalâluddîn al-Suyûtî condemned the prohibition of making Jews and Christians as guardians/meeting friends/leaders on the grounds of following qâ'idah al-Ashl fi al-Nahy li al-Tahrim